2020
DOI: 10.1155/2020/6950206
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine Huzhen Tongfeng Formula Effectively Attenuates Gouty Arthritis by Inhibiting Arachidonic Acid Metabolism and Inflammatory Mediators

Abstract: The Chinese herbal medicine, Huzhen Tongfeng Formula (HZTF), derived from traditional Chinese medicine (TCM) practice, has recognized therapeutic benefits for gouty arthritis (GA). HZTF is currently in the late stage of approval process as a new anti-GA drug application. However, the underlying mechanism of HZTF as an antigout medication is unclear. In this study, we combined network pharmacology and experimental validation approaches to elucidate the mechanism of action of HZTF. First, the relative drug-disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The network consisted of 105 nodes and 373 edges, with the innermost and purple diamond representing the 35 validated compounds of TFDC, the middle and red circle indicating the 50 gout-related targets, and the outermost “V” shape in yellow indicating the 20 enriched KEGG pathways. It is worth noting that the arachidonic acid metabolism pathway was highly enriched in the KEGG pathway analysis, which played an important role in gout treatment ( Graham et al, 2013 ; Napagoda et al, 2018 ; Deng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The network consisted of 105 nodes and 373 edges, with the innermost and purple diamond representing the 35 validated compounds of TFDC, the middle and red circle indicating the 50 gout-related targets, and the outermost “V” shape in yellow indicating the 20 enriched KEGG pathways. It is worth noting that the arachidonic acid metabolism pathway was highly enriched in the KEGG pathway analysis, which played an important role in gout treatment ( Graham et al, 2013 ; Napagoda et al, 2018 ; Deng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Under normal physiological conditions, the expression of COX‐2 is minimal; however, when the kidney is stimulated, its expression is increased (Liu et al, 2019; Yang et al, 2020). In particular, COX‐2 is the main source of prostacyclin (PGI2) (Deng et al, 2020). Once AA is released, it is metabolized by the PTGS isoenzymes PTGS‐1 and PTGS‐2 (Zhou et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies revealed that oral administration of HTF reduced ankle swelling and inflammatory cell infiltration in rabbits with gouty arthritis. In vitro, HTF inhibited the expression of COX-1, COX-2, and 5-lipoxygenase [145]. Furthermore, HTF can be used to treat gouty arthritis by inhibiting the release of proinflammatory factors such as IL-1, IL-6, TNF-α, and ASC oligomerization [146].…”
Section: Tcm Prescription For Goutmentioning
confidence: 99%